Causes of death in long‐term survivors of head and neck cancer. Issue 10 (22nd February 2014) - Baxi, Shrujal S.; Pinheiro, Laura C.; Patil, Sujata M.; Pfister, David G.; Oeffinger, Kevin C.; Elkin, Elena B.
<x xml:space="preserve">Abstract</x> BACKGROUND Survivors of head and neck squamous cell carcinoma (HNSCC) face excess mortality from multiple causes. METHODS We used the population‐based Surveillance, Epidemiology, and End Results (SEER) cancer registry data to evaluate the causes of death in patients with nonmetastatic HNSCC diagnosed between 1992 and 2005 who survived at least 3 years from diagnosis (long‐term survivors). We used competing‐risks proportional hazards regression to estimate probabilities of death from causes: HNSCC, second primary malignancy (SPM) excluding HNSCC, cardiovascular disease, and other causes. RESULTS We identified 35, 958 three‐year survivors of HNSCC with a median age at diagnosis of 60 years (range = 18‐100 years) and a median follow‐up of 7.7 years (range = 3‐18 years). There were 13, 120 deaths during the study period. Death from any cause at 5 and 10 years was 15.4% (95% confidence interval [CI] = 15.0%‐15.8%) and 41.0% (95% CI = 40.4%‐41.6%), respectively. There were 3852 HNSCC deaths including both primary and subsequent head and neck tumors. The risk of death from HNSCC was greater in patients with nasopharynx or hypopharynx cancer and in patients with locally advanced disease. SPM was the leading cause of non‐HNSCC death, and the most common sites of SPM death were lung (53%), esophagus (10%), and colorectal (5%) cancer. CONCLUSIONS Many long‐term HNSCC survivors die from cancers other than HNSCC and from noncancer causes. Routine follow‐up care for HNSCC survivors should expand beyond surveillance for recurrent and new head and neck cancers. Cancer 2014;120:1507–1513. © 2014 American Cancer Society.